Pengaruh Perubahan Tutupan Lahan dan Indeks Pembangunan Manusia Terhadap Kejadian TB Paru Di Provinsi Lampung - Widianningrum, Wahyu; Bakri, Samsul; Kurniawan, Betta; Darmawan, Arief; Suwandi, Jhons Fatriyadi; Nurcahyani, Nuning; Wulandari, Christine (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Land cover change is one of the major contributors to environmental degradation and can significantly alter the physical environment. These alterations in the physical environment may have substantial implications for human health. One of the notable health impacts associated with such changes is the increased incidence of tuberculosis. Tuberculosis cases are linked to the proliferation of Mycobacterium tuberculosis, which thrives in environments with high humidity levels. This study employs linear regression analysis to examine the influence of various types of land cover—namely, plantation areas, mixed agriculture, residential zones, and rice fields—on tuberculosis incidence. Additionally, the study incorporates Human Development Index (HDI) and economic growth rate as proxies for human development in Lampung Province. The findings, based on t-test statistical analysis, reveal that plantation land cover (P-value = 0.045) and the rate of economic growth (P-value = 0.001) have a statistically significant effect on tuberculosis incidence in the region. In contrast, other land use types and the Human Development Index do not exhibit a significant relationship with the number of tuberculosis cases. Based on these results, it is recommended that the government formulate credible and evidence-based regulations concerning future land use planning.